Pathogenesis of thoracic ossification of the ligamentum flavum - Zhang, Chi; Chang, Yanan; Shu, Li; Chen, Zhongqiang (Frontiers in Pharmacology, 2024)
Thoracic ossification of the ligamentum flavum (TOLF) is characterized by ectopic ossification of the ligamentum flavum in the thoracic spine and is considered the main cause of thoracic spinal stenosis and spinal cord disease. Osteoblast specific transcription factor Osterix (Osx) is required for bone formation, and there is no bone formation or ossification without Osx.Surgical intervention is recognized as the only effective method for TOLF treatment with set of complications. However, underlying mechanisms of TOLF are not well understood. This paper summarizes the pathogenesis of TOLF. Some relevant factors have been discussed, such as mechanical stress, genetic susceptibility genes, endocrine and trace element metabolism abnormalities, which may associate with TOLF. More recent studies using proteomics technology and RNA sequencing approach have discovered that some new factors participate in TOLF by upregulation of Osx gene expression including inflammatory factors. TOLF is a unique disease involving multiple factors. On the other hand, studies on TOLF pathogenic mechanism may provide new ideas for finding possible upstream regulatory factors of Osx and further developing novel drugs to stimulate new bone formation to treat osteoporosis.